2017
DOI: 10.1177/0300060517716502
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ondansetron for spinal anesthesia during cesarean section: a meta-analysis of randomized trials

Abstract: ObjectiveTo investigate the efficacy and safety of ondansetron during cesarean section under spinal anesthesia.MethodsWe sought randomized controlled trials (RCTs) on ondansetron during spinal anesthesia for cesarean section in The Cochrane Library, PubMed, MEDLINE, and Web of Science from their inception to September 2016.ResultsAltogether, 21 RCTs were included in this study. Meta-analysis showed that the ondansetron group had a lower incidence of nausea/vomiting and bradycardia than the placebo group during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
3
27
2
3
Order By: Relevance
“…The inconsistency between direct and indirect comparisons for rates of intra‐operative nausea and vomiting may have been due to differences in the way trials reported this outcome or variation in confounding factors, such as the use of sodium citrate, which may increase the rate of nausea , or prophylactic anti‐emetics that reduce the rate . Other factors that may have contributed to inconsistency include the dose of intrathecally injected local anaesthetic or adjuvants, the surgical approach or other local practices that may have influenced the risk of intra‐operative nausea but were unrelated to maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency between direct and indirect comparisons for rates of intra‐operative nausea and vomiting may have been due to differences in the way trials reported this outcome or variation in confounding factors, such as the use of sodium citrate, which may increase the rate of nausea , or prophylactic anti‐emetics that reduce the rate . Other factors that may have contributed to inconsistency include the dose of intrathecally injected local anaesthetic or adjuvants, the surgical approach or other local practices that may have influenced the risk of intra‐operative nausea but were unrelated to maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…described a lowered rate of bradycardia following administration of 5‐HT 3 antagonists before SPA among women undergoing CD. A meta‐analysis performed by Zhou et al . also found reduced bradycardia among patients treated with ondansetron.…”
Section: Discussionmentioning
confidence: 89%
“…Previous investigations of dosage underpinned the decision to use 3 mg of granisetron at University Hospital Frankfurt. Different regimens and type of 5‐HT 3 receptor antagonists have been used in previous studies . Varying pharmacologic properties of different 5‐HT 3 receptor antagonists impede comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance of such headaches, some attempts have been made to reduce PDPH. As the effectiveness of dexamethasone and ondansetron in reducing the headaches caused by spinal anesthesia has not been thoroughly compared against one another and considering the high prevalence rate of caesarean operation over recent years (1,12,13), we decided to study the effect of adding these two drugs during spinal anesthesia in reducing PDPH among women candidated for elective caesarean.…”
Section: Introductionmentioning
confidence: 99%